Lahirnya Zaman Bahagia: Transformasi Teologi Pribumi di Tanah Papua - I Ngurah Suryawan (JSW (Jurnal Sosiologi Walisongo), 2017)
This article discusses oral traditions of indigenous theologies that various communities in Papua believe about their God as life savers. The indigenous theology has historically played an important role in shaping the knowledge of religion, customs, and culture into their life orientations. The indigenous theologies include Ugatamee, Hai and Koreri and their oral traditions experienced transformation in the presence of religion. The tension between indigenous theology and the values of the gospel in Christianity in particular has a serious impact on religious orientation as well as the culture of society. The spread of Christianity, especially the one that touches people's lives, leads to a great transformation of people's trust in God. The great transformation was in the land of Papua, one of which was brought about by the influence of religious education, which subsequently played a major role in the construction of their religious life and experience.